Nano-carriers for the Treatment of Tuberculosis - Gilani, Sadaf J.; Ameeduzzafar; Jafar, Mohammed; Shakil, Kashif; Imam, Syed S. (Recent Patents on Anti-Infective Drug Discovery, 2017)
Background: Nano size based drug delivery systems are an emerging technique with the potential to develop new strategies involving handling of drugs at the nanometer scale. There are many nano-based drug delivery systems that have been extensively reported as drug carriers for the treatment of tuberculosis. Methods: There are numerous nano sized drug delivery systems like lipid nanoparticles, polymeric micelle, carbon nanotubes and polymeric nanoparticles that have been reported for a long time to treat diseases. There are a number of drawbacks in conventional TB dosage forms such as the development of multiple drug resistance, resulting in intolerable toxicity and high drug dose required. So, to overcome the drawbacks of conventional therapy, there is a need for a new drug delivery system with an aim to reduce the side effects of drug treatment. Nano-sized based drug delivery systems have considerable potential for the treatment of tuberculosis. These delivery systems have several advantages like high stability, high loading capacity, the feasibility of incorporation of both hydrophilic and hydrophobic drugs, and feasibility of variable routes of administration, and prolonged drug release from the matrix. These advantages enable enhanced drug solubility, bioavailability, reduced dosing frequency, high targeting, and may resolve the problem of non adherence to prescribed therapy, which is one of the major obstacles in the control of tuberculosis epidemics. Conclusion: This article gives an exhaustive review of patents and research papers published over the years on the challenges, the current treatment therapy of the disease faces, and potential advantages of nano sized formulations to offer more effective treatment and prevention for tuberculosis.
Keywords: polymeric nanoparticle